(untitled) (Journal of the College of Basic Education, 2022)
Extraposition can be defined as a process by which an element is moved from its normal position to another position that is at or near the end of the sentence. It is regarded as a stylistic rule, the failure to extrapose can result in awkward constructions that may even cause interpretation difficulties. It is mostly used in the formal writings more than in the informal ones. The extraposition strategy is in general used with certain verbs such as (seem, appear, follow, …..) . It has two cases: extraposition of a clausal subject and extraposition of a clausal object. In addition, it has several syntactic constructions such as that-clause, infinitive and gerund. This study is limited with studying the clausal subject extraposition and also it focuses on the use of the clausal subject extraposition in two selected registers: political speeches and religious speeches showing the cases and the forms of extraposition that are used in these two registers. The issues that are going to be discussed are: the concept of extraposition, its cases and syntactic constructions the meaning of each case and construction the reasons for using extraposition in general and its constructions in specific the frequency of clausal subject extraposition in political and religious speeches It has been found that the clausal subject extrapostion is used more in the political speeches than in the religious speeches. that -clause is used more than the other forms.